GAPDH and β-actin protein decreases with aging, making Stain-Free technology a superior loading control in Western blotting of human skeletal muscle - Vigelsø, Andreas; Dybboe, Rie; Hansen, Christina Neigaard; Dela, Flemming; Helge, Jørn W.; Guadalupe Grau, Amelia (Journal of applied physiology (1985), 2015)
Reference proteins (RP) or the total protein (TP) loaded is used to correct for uneven loading and/or transfer in Western blotting. However, the signal sensitivity and the influence of physiological conditions may question the normalization methods. Therefore, three widely used reference proteins [β-actin, glyceraldehyde 3-phosphate dehydrogenase (GAPDH), and α-tubulin], as well as TP loaded measured by Stain-Free technology (SF) as normalization tool were tested. This was done using skeletal muscle samples from men subjected to physiological conditions often investigated in applied physiology where the intervention has been suggested to impede normalization (ageing, muscle atrophy, and different muscle fiber type composition). The linearity of signal and the methodological variation coefficient was obtained. Furthermore, the inter- and intraindividual variation in signals obtained from SF and RP was measured in relation to ageing, muscle atrophy, and different muscle fiber type composition, respectively. A stronger linearity of SF and β-actin compared with GAPDH and α-tubulin was observed. The methodological variation was relatively low in all four methods (4–11%). Protein level of β-actin and GAPDH was lower in older men compared with young men. In conclusion, β-actin, GAPDH, and α-tubulin may not be used for normalization in studies that include subjects with a large age difference. In contrast, the RPs may not be affected in studies that include muscle wasting and differences in muscle fiber type. The novel SF technology adds lower variation to the results compared with the existing methods for correcting for loading inaccuracy in Western blotting of human skeletal muscle in applied physiology.